Organizational cynicism, work related quality of life and organizational commitment in employees - Tahreem Yasin; Shazia Khalid (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
The research intended to explore relationship between organizational cynicism, work related quality of life and organization commitment in employees. The literature on organizational cynicism and organizational commitment revealed that cynicism has intense effects on organizational commitment. Moreover the effect of work related quality of life as a mediating variable was also inspected. The data was collected through questionnaires and sample comprised of 150 male employees between the age range of 28- 50 years (M age=32.11, SD= 5.36) working at managerial position of different companies of Lahore with a minimum experience of 3 years. The results of the study concluded that three of the dimensions of organizational cynicism had significant negative relationship with five of the dimensions of work related quality of life and two of the dimensions of organizational commitment. Moreover two of the dimensions of work related quality of life had significant negative relationship with two of the dimensions of organizational commitment. Structural Equation Modeling through AMOS revealed that working conditions mediated the relationship between affective cynicism and affective commitment. The main limitation of the study is the sample used, that it includes only males and from the private companies of Lahore. Implications for present study in organizations will be to lessen the negative attitudes in employees so they can work effectively and increase their productivity in respective companies and the work efficiency, quality of work life and commitment should be improved. This study aims to add to the knowledge in this area by exploring how cynicism affects quality of working life and organizational commitment that is almost under-research in Pakistan.
Keywords: 330